Sistem Pendukung Keputusan Pemilihan Penerima Bantuan Sosial Menggunakan Metode Electre & Roc - Siringoringo, Franky (Management of Information System Journal, 2023)
Selection is a procedure making to the decision group where people who meet the requirements are eligible to receive such assistance, pick someone to ensure beneficiaries are still using subjective judgment.The decision support system used is a combination of two methods. First, using the Elimination and Choice Expressing Reality (ELECTRE) method, which is a multi-criteria decision-making method based on the concept of outranking using paired comparisons of alternatives based on each appropriate criterion. This method is implemented using ROC (Rank Order Centroid) as weighting